STRATEGI PEMASARAN JASA FREIGHT FORWARDING JAKARTA - Arif Hernawan; Yunita Triyani Tamba; Muhammad Rifni (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The aim of this research is to find out the external and internal factors and to analyze strategy formulation to increase freight forwarding marketing services. This research used SWOT analysis, internal and external matrixes. The results based on the SWOT analysis are the strength 3.83, the weaknesses 3.40, with the margin 0.43, and the opportunity 3.57, the threat 3.18, with the margin 0.39. The company takes place in quadrant I of SWOT in which the company has big strength and opportunity, so that the company is in SO strategy. Based on IE matrix, it is found that the internal factor 3.13, external factor 3.00, so that the company is in cell I which is in growing and developing position. So, the strategies that can be applied are market penetration, market development, and product development or the strategy of integration backwards, forwards and horizontal. Moreover, the results based on SWOT analysis diagram and IE matrix also found that alternative strategies are market penetration, market development, product development, backward integration, forward integration, horizontal integration.